2020
DOI: 10.3390/children7080096
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Intravenous Propofol and Ketorolac to a Sevoflurane Anesthetic Lessens Emergence Agitation in Children Having Bilateral Myringotomy with Tympanostomy Tube Insertion: A Prospective Observational Study

Abstract: The aim of this prospective observational study was to determine if children undergoing bilateral myringotomy and tympanostomy tube insertion with a sevoflurane anesthetic plus intravenous propofol and ketorolac experienced a lower incidence of emergence agitation than those receiving a sevoflurane anesthetic alone. Duration of procedure, length of stay in post-anaesthesia care and level of nursing effort required to care for patients were also assessed. In this study, 49 children younger than 13 years of age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…6 Tube insertion in children is nearly always performed in a surgical setting under general anesthesia, but interest in office insertion has grown because of convenience, possible cost savings, and concerns over potential anesthetic-related adverse events. These adverse events include emergence agitation (delirium) in up to two-thirds of children, 7 death ranging from 1 in 10,000 to 100,000 anesthetics delivered (but rarely in children without serious underlying medical problems), 8 and potential neurotoxicity. This last concern prompted the FDA to institute a label change on inhalational anesthetics, plus midazolam and propofol, warning that “exposure to these medicines for lengthy periods of time or over multiple surgeries or procedures may negatively affect brain development in children younger than 3 years.” 9…”
Section: Discussionmentioning
confidence: 99%
“…6 Tube insertion in children is nearly always performed in a surgical setting under general anesthesia, but interest in office insertion has grown because of convenience, possible cost savings, and concerns over potential anesthetic-related adverse events. These adverse events include emergence agitation (delirium) in up to two-thirds of children, 7 death ranging from 1 in 10,000 to 100,000 anesthetics delivered (but rarely in children without serious underlying medical problems), 8 and potential neurotoxicity. This last concern prompted the FDA to institute a label change on inhalational anesthetics, plus midazolam and propofol, warning that “exposure to these medicines for lengthy periods of time or over multiple surgeries or procedures may negatively affect brain development in children younger than 3 years.” 9…”
Section: Discussionmentioning
confidence: 99%
“…Emergence agitation is a very common complication after surgery, especially for school-aged children with ages 3 to 5 years. 4 Although agitation during the recovery period is self-limiting, it increases the risk of children's self-harm, reduces parental anxiety and satisfaction, prolongs the hospital stay, and increases additional medical expenses. 32 Among them, sevoflurane anesthesia in children has a higher incidence of agitation during the recovery period, which can increase the incidence of agitation during the recovery period in children compared with propofol.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Therefore, it is widely used in the induction and maintenance of pediatric anesthesia. 4 However, the incidence of agitation during recovery from sevoflurane anesthesia is generally higher. Relevant studies have shown that the incidence of agitation during recovery from sevoflurane inhalation anesthesia can be as high as 10% to 80%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Emergence agitation and delirium are common pediatric anesthesia complications. A prospective observational study found a single dose of propofol at the end of a sevoflurane-based myringotomy may decrease postoperative agitation [ 15 ].…”
Section: Pediatric Anesthesia Specific Considerationsmentioning
confidence: 99%